Pelaksanaan E-Government Pendaftaran Tanah Guna Terwujudnya Kepastian Hukum Dalam Kepemilikan Tanah Di Kabupaten Sumenep - Iwan Permadi; Azna Abrory Wardana (Jurnal VOK@SINDO, 2020)
Land registration is one of the Government's efforts to provide legal certainty for subjects holding rights to land. Land Registration Policy according to Government Regulation Number 24 of 1997 concerning Land Registration recognizes 2 land registration systems, namely sporadically and systematically. However, in the PP there are still no rules regarding land registration that can be done sporadically or systematically based on information and communication technology. As an area that is included in 100 Regencies / Cities that implement smart-cities in Indonesia, Sumenep Regency continues to improve public services for the community with e-government systems. However, the application of e-government in land registration in Sumenep Regency is still constrained by several factors. This research was assessed using empirical juridical research methods using a sociological juridical approach.